2012
DOI: 10.1074/jbc.m112.371476
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons (PAHs) Mediate Transcriptional Activation of the ATP Binding Cassette Transporter ABCB6 Gene via the Aryl Hydrocarbon Receptor (AhR)

Abstract: Background: ABCB6 is an ATP binding cassette transporter that regulates heme biosynthesis. Results: Polyaromatic hydrocarbons increase heme synthesis in liver by activating ABCB6 expression via the aryl hydrocarbon receptor. Conclusion: ABCB6 is required for PAH-mediated induction of heme biosynthesis. Significance: ABCB6 expression might be clinically relevant in polyaromatic hydrocarbon-induced porphyrias and carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 57 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…Cellular Protoporphyrin IX Measurements-Intracellular protoporphyrin IX concentration was measured as previously described (21). Briefly, cells were harvested and washed once with PBS.…”
Section: Materials-8-azido-[␣-mentioning
confidence: 99%
“…Cellular Protoporphyrin IX Measurements-Intracellular protoporphyrin IX concentration was measured as previously described (21). Briefly, cells were harvested and washed once with PBS.…”
Section: Materials-8-azido-[␣-mentioning
confidence: 99%
“…In summary, PEPT1 overexpression or ABCG2 suppressing caused increase of intracellular PpIX accumulation24. Other studies showed that ABCB6 overexpression induced increase of PpIX12 and ABCB6 suppressing induced decrease of PpIX25 respectively. Therefore, we focused on these 3 transporters.…”
Section: Resultsmentioning
confidence: 68%
“…P450 Promoter-LUC Reporter Assays in HepG2 Cells-Promoter-reporter luciferase activity assays were performed as previously described (29). Briefly, HepG2 cells at ϳ60% confluency were transfected with either Preparation of Mouse Liver Extracts-Metabolite extraction from liver samples was done as described (36).…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting-Western blot analysis of mitochondrial and microsomal proteins was carried out as previously described (28,29). Polyclonal primary antibodies were used to detect P450 oxidoreductase (catalog no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation